2001
DOI: 10.1017/s0031182000007058
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the component community structure of haemoparasites in bank voles (Clethrionomys glareolus) from the Mazury Lake District region of Poland

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk The prevalence and abundance of infections with haemoparasites were studied over a 3 year period in Clethrionomys gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
76
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 16 publications
12
76
4
Order By: Relevance
“…2% in C. glareolus and only 2 . 2 % in the wood mouse Apodemus sylavaticus ; Bajer et al (2001) found an average prevalence of 15 % in C. glareolus over 3 years ; and Pawelczyk et al (2004) reported prevalence levels ranging from 20 % to less than 10 % in M. arvalis over 4 years. However, the differences between these and the present results may largely be due to differences in diagnostic methods.…”
Section: Discussionmentioning
confidence: 95%
“…2% in C. glareolus and only 2 . 2 % in the wood mouse Apodemus sylavaticus ; Bajer et al (2001) found an average prevalence of 15 % in C. glareolus over 3 years ; and Pawelczyk et al (2004) reported prevalence levels ranging from 20 % to less than 10 % in M. arvalis over 4 years. However, the differences between these and the present results may largely be due to differences in diagnostic methods.…”
Section: Discussionmentioning
confidence: 95%
“…increase when the population density is high and fall when it is low (Lewis, 1968 ;Montgomery and Montgomery, 1988 ;Haukisalmi and Henttonen, 1990), and the substantial drop in the prevalence of S. petrusewiczi between 1999 (when vole densities were very high ; 18 . 8/1000 trap hours at Urwitałt, see Bajer et al 2001) and 2002 (when they were lower at 8 . 6, 8 .…”
Section: Journalscambridgeorgmentioning
confidence: 95%
“…The parasites in 100 fields of vision (approx. 100,000 red blood cells) were counted as described previously (Bajer et al 2001;Kloch et al 2010).…”
Section: Parasite Screeningmentioning
confidence: 99%
“…Norrdahl and Korpimäki 2005;Borkowska et al 2009) and parasitological (e.g. Bajer et al 2001;Burthe et al 2008) studies, they were also subject of several studies of MHC polymorphism in the wild (e.g. Oliver et al 2009;Kloch et al 2010).…”
Section: Introductionmentioning
confidence: 99%